Modelling and switching simulation of gate turn-off thyristor using finite element method - Norainon, Mohamed (2010)
The gate turn-off (GTO) thyristor has the best voltage blocking and current conducting capabilities among all known high power semiconductor switching devices. The switching characteristics of a GTO thyristor are influenced by doping profile, material properties, lifetime and mobility of holes and electrons. Recently, most of the research on GTO thyristor is strictly experimental and has focused on their physical performances. On the other hand, the internal behaviour of GTO thyristor is not well understood. The best accuracy switching waveforms and the internal behaviour of the device can only be addressed by device simulation. Physical models (Poisson equation, drift-diffusion and current-continuity equations) of GTO thyristor are valuable for studying the internal behaviour of the device is used in the simulation. These equations are numerically solved by using finite element method. This project presents: the modelling and switching simulation of GTO thyristor device by developing a device simulation software. The software is designed by using MATLAB Graphical User Interface (GUI) development environment. The device model has been developed based on the device structure and operation. The thesis focuses on the study of a comparison between silicon and silicon carbide GTO thyristor in terms of switching time performances and efficiency at the system level.